Kegiatan Pengabdian Masyarakat dalam Rangka Edukasi Masyarakat Mengenai Penapisan GERD dan Dispepsia pada Lanjut Usia - Alfianto Martin; Alexander Halim Santoso; Edwin Destra; Farell Christian Gunaidi; Muhammad Kharis Mahdaviqia; Raden Seliwat Agung Aditya; Kasvana Kasvana; Syilvia Cendy Enike (Jurnal Pengabdian Bidang Kesehatan, 2024)
Gastroesophageal reflux disease (GERD) is a chronic gastrointestinal disorder characterized by regurgitation of gastric contents into the esophagus, causing a variety of clinical symptoms such as heartburn, regurgitation, and atypical presentations such as chest pain, chronic cough, and asthma. In the elderly, GERD is very common, often with atypical symptoms and has a higher risk of complications, including esophagitis, Barrett's esophagus, and esophageal cancer. Functional dispepsia, another common gastrointestinal disorder, affects more than 20% of the population and is associated with significant negative impacts on quality of life and health care costs. This community service activity aims to screen for GERD and dispepsia in the elderly population through the Plan-Do-Check-Act (PDCA) approach. The activity was carried out at Panti Bina Bhakti, South Tangerang, involving 93 elderly participants aged over 65 years. The results showed that 64 people (68.82%) had a 50% chance of GERD, 21 people (22.58%) had a 79% chance of GERD, and 6 people (6.45%) had an 89% chance of GERD. Screening for GERD and dispepsia in the elderly is very important for early detection and timely intervention, which can prevent disease progression and reduce the risk of complications.